Informing Sustainability Education in Academic Libraries Through Community Engagement: Evidence From a Rural Green Library in Indonesia - Anwar, Rully Khairul; Rejeki, Diah Sri; Aunillah, Rinda; Surya, Ibrahim Adi; Agustine, Merryam (Evidence Based Library and Information Practice, 2025)
Objective – This research investigates how a rural community library contributes to sustainability education by generating practice-based evidence promoting environmental literacy that is participatory, culturally grounded, and responsive to local contexts. The study focuses on Perpustakaan Alam Malabar in Mekarsari Village, West Java, Indonesia and examines how the library integrates ecopedagogical strategies to foster ecological awareness within the community.Methods – A qualitative single-case study design was applied. Data were gathered through semi-structured interviews, participant observation, and document analysis and were analyzed using the interactive model developed by Miles, Huberman, and Saldaña. The researchers took part in several community-based programs hosted by the library, such as mobile literacy sessions (melapak), environmental discussions, film screenings, gardening activities, and the annual Rawat Bumi Festival. Data reliability was strengthened through triangulation and member checking.Results – The findings indicate that Perpustakaan Alam Malabar has successfully redefined the library as a participatory learning hub that supports environmental literacy in everyday life. The library’s approach blends scientific insights with local wisdom and community-based action, creating an educational environment that stimulates cognitive, emotional, and behavioural engagement. Nonetheless, the model faces several constraints, including reduced local participation, a lack of institutional policy support, and the growing influence of external stakeholders. To navigate these challenges, the library has implemented adaptive strategies, including training local facilitators, fostering cross-sector partnerships, and promoting culturally responsive communication.Conclusion – The study demonstrates that community libraries—especially in rural settings—can serve as effective platforms for sustainability education. The Perpustakaan Alam Malabar model offers a replicable, evidence informed model that practitioners can adapt to align literacy initiatives with ecological values and local engagement. In addition to its empirical contributions, the study advances a conceptual perspective on libraries as inclusive, transformative, and community-driven spaces for ecological learning and advocacy.